IMPACT OF CORN GRAIN MOISTURE AT HARVESTING TO AGRONOMIC TRAITS IN SUBSEQUENT GENERATION - & Baktash, Al-kazaali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted during spring and fall seasons, 2015 , at the fields of Field Crop Department – College of Agriculture –University of Baghdad . The objective was to evaluate the impact of corn grain moisture at harvesting of original population to some agronomic traits in subsequent generation of the variety 5018. In spring season 2015 , a seeds population of this variety were planted. When the moisture of ear grains was go to the first treatment (37-42%) , ten ears were harvested . Ear harvesting dates were performed manually when the grains had 37-42% , 34-36% , 30-33% , 25- 28% and 19-22% moisture content . Ten ears were harvested from each treatment . In fall season 2015 , varietal trail was carried out to the five treatment materials , using Randomized Complete Bock Design , with four replicates . The results were revealed significant differences among treatments in number of days from planting to maturity , crop growth rate. g. plant .day -1 , crop growth rate . g .m2. day -1 and grain yield kg. m-2 . The highest grain yield ( 1.07 kg. m-2 ), was produced from plant seeds , which harvested with moisture (19-22)% .It can be concluded the best harvesting moisture to produce seeds for plating in subsequent generation was ( 19-22 )% .